RANCANG BANGUN APLIKASI CLUSTERING DATA MINING MENGGUNAKAN METODE K-MEANS DAN K-MODES - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Strategies and policies in a profit-oriented organization also have a social mission (public service) that prioritizes the service to the customer. The development of information system and information technology will impact on a competitive competition. This development also applies in the world of certification that requires the manager to build and develop information system to help the business activities, to achieve organizational goals and services for stakeholders, especially those which related to data, information, technology and application. We found some cases of information system management failure in achieving organizational objectives because the utilization is not in accordance with the direction and objectives of the organization. The system will analyze the relationship pattern of goods towards the goods order based on needs and usage. Furthermore, the patterns will be recognized so that we can obtain the composition set of criteria to order the goods. To find the patterns and information from a collection of reservation data into a decision-making material. Therefore, the writers make a study with the title